ON THE LARVAL STAGES OF POLYMORPHUS SPINDLATUS (ACANTHOCEPHALA: POLYMORPHIDAE) FROM A NEW FISH HOST, OREOCHROMIS NILOTICUS, IN PERU - M. Amin, Omar (2010)
Larval stages of the acanthocephalan Polymorphus spindlatus Amin & Heckmann, 1991(Polymorphidae) were obtained from the intestine of tilapia, Oreochromis niloticus Linnaeus, 1758 (Pisces: Cichlidae) in Villa Swamps, Lima, Peru during 2006. Cystacanth stages were recovered from the intestine, observed live, and documented photographically. Early stages had an ovoid proboscis that developed into the spindle-shaped form characteristic of the adult proboscis only in the late cystacanth stage. Form and pattern of adult proboscis hooks were evident in the younger larvae. The constriction in the trunk of the early stages was lost in the developed cystacanth. The morphology of the spindle-shaped trunk and other features of the cystacanth from the fish host were similar to those reported for cystacanths previously reported from the body cavity of fish hosts in Lake Titicaca, Peru.